Green Technology and Renewable Energy Projects - Baboli, Mostafa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Currently, water and energy are among the world biggest challenges. All countries working on increasing industries and searching for progress need energy. Beside the limitation on the energy in the world, the aspect that has limited the use of energy is global warming. Fossil fuels are mostly used in the industries produce greenhouse gasses that cause trapping of the heat in the atmosphere and thus lead to temperatures rising and climate change. The importance of green energy is that it does not have the negative effect of fossil fuels and does not release carbon dioxide as the main greenhouse gas through combustion. This book contains some new studies about the production of renewable energies and applications of green technologies in various processes. The book is useful for researchers in the field of green technologies and also post-graduate students who are interested in expanding their knowledge of novel technologies and green fuels. It contains six chapters. In Chapter 1, a microbial fuel cell was studied and optimized. In Chapter 2, an autonomous model that can be used in cars and agriculture was reviewed. Chapter 3 studies the dehumidification capacity of water walls. Chapter 4 discusses the performance of conventional and unconventional single U-Tube pipe configurations. Chapter 5 studies the power generation table of 40 different locations in Oman. Finally, in Chapter 6 the role of renewable energy in south Asian countries is discussed.